Avaliação dos mecanismos centrais e periféricos envolvidos no fenótipo cardiovascular de ratos TGR(A1-7)7371 que superexpressam Angiotensina-(1-7) no cérebro - Daniele Teixeira Alves (2018)
In the central nervous system, the ACE2-angiotensin-(1-7)-Mas receptor arm of the renin angiotensin system (RAS) plays an important role in areas related to cardiovascular control. Recently, we obtained a transgenic rat line that express an angiotensin-(1-7)-producing fusion protein under regulation of the GFAP promoter, the [TGR(A1-7)7371]. The main cardiovascular characteristic of these rats is a lower baseline blood pressure. This result, a genetic modification in an animal with normotensive background would have induced a hipotensive phenotype, is of great physiological significance and reinforces the role of this axis of the RAS for the control of blood pressure. The objective of the present study was to determine the central and peripheral mechanisms involved in this phenotype. First, we evaluated the hemodynamic measurements and the plasma levels of the atrial natriuretic peptide (ANP) in [TGR(A1-7)7371] rats. Blood flow distribution, cardiac output, cardiac index and total peripheral resistance were investigated by using fluorescent microspheres and plasma levels of the ANP by enzymatic immunoassay (ELISA). Next, we evaluated the distribution of transgene expression by immunofluorescence and quantified by RT-PCR and qRT-PCR the expression of the transgenic mRNA [GFAP-Ang (1-7)] in areas/nucleus and cell types of the brain and in peripheral tissues of theses animals. TGR(A1-7)7371 rats presented lower MAP, as expected, and plasma increase of ANP. Further, TGR rats showed a significant increase in blood flow in different tissues (kidneys, mesentery, muscle, spleen, brown fat, heart and skin), which resulted in a decrease in total peripheral resistance. Higher intensity labeling for the fusion protein was identified in medullary areas related with cardiovascular control, as the rostral and caudal ventrolateral medulla (RVLM and CVLM), nucleus ambiguus (Amb), nucleus tractus solitarius (NTS) and dorsal motor nucleus of the vagus nerve. In the hypothalamus, the TGR(A1-7)7371 rats showed immunoreactivity to the fusion protein only in the supraoptic nucleus (SON). Immunostaining for fusion protein has also been observed in other areas not directly involved with cardiovascular control, such as the hippocampus, amygdala, cortex, thalamus, striatum and raphe nuclei. Surprisingly, fusionprotein was preferentially present in neurons and transgenic mRNA expressed in various peripheral tissues. However, immunoreactivity for fusion protein was not observed in peripheral tissues, such as the aorta, heart, lung and testis. The expression of an angiotensin-(1-7) producing fusion protein in areas involved with cardiovascular control in the brain was consistent with the previous cardiovascular findings observed in these rats. These data support and extend previous results showing a potent hypotensive action induced by the long-term increase of Ang-(1-7) in the brain, which is determined by peripheral vasodilation and increased ANP levels. These data also establish a new animal model to study the impact of increase in Ang-(1-7) cerebral levels in cardiovascular diseases.